2016
DOI: 10.1103/physreva.93.043618
|View full text |Cite
|
Sign up to set email alerts
|

Modified interactions in a Floquet topological system on a square lattice and their impact on a bosonic fractional Chern insulator state

Abstract: We propose a simple scheme for the realization of a topological quasienergy band structure with ultracold atoms in a periodically driven optical square lattice. It is based on a circular lattice shaking in the presence of a superlattice that lowers the energy on every other site. The topological band gap, which separates the two bands with Chern numbers +/-1, is opened in a way characteristic of Floquet topological insulators, namely, by terms of the effective Hamiltonian that appear in subleading order of a h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 69 publications
(99 reference statements)
0
16
0
Order By: Relevance
“…Numerical studies based on the exact diagonalization (Anisimovas et al, 2015;Račiūnas et al, 2016) suggest that this smearing out tends to have a negative impact on the possible stabilization of fractional-Chern-insulator states in Floquet topological band structures recently proposed by Grushin et al, 2014.…”
Section: Floquet Engineering Of Interactionsmentioning
confidence: 99%
“…Numerical studies based on the exact diagonalization (Anisimovas et al, 2015;Račiūnas et al, 2016) suggest that this smearing out tends to have a negative impact on the possible stabilization of fractional-Chern-insulator states in Floquet topological band structures recently proposed by Grushin et al, 2014.…”
Section: Floquet Engineering Of Interactionsmentioning
confidence: 99%
“…We have also found that ramping up the interaction strengths, driving-induced heating is significantly enhanced, until a saturation value is reached roughly when the ratio U s /J s reaches values of 3. This saturation is a promising result regarding the possibility to use Floquet engineering for the preparation of strongly correlated states of matter such as fractional Chern insulators [46][47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…An entire sub-domain of "Floquet Topological Insulators" [41] has emerged as a result, which constitutes those systems that exhibit topological ground states and edge phenomena in the presence of certain time-dependent periodic potentials [42]. They have offered unprecedented control and freedom to engineer new topological phases and edge state(in some cases Majorana modes) behaviors [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] as well as a knob to study topological phase transitions in cold-atom or photonic crystal setups [63][64][65][66][67][68][69]. The theoretical classification of Floquet topological insulators and the identification of valid topological invariants that correctly characterize the bulk-edge correspondence for these systems is an on-going effort [70][71][72][73][74][75][76][77].…”
Section: Introductionmentioning
confidence: 99%
“…The recent success in realizing the Haldane model experimentally [30] within the framework of ultracold atoms in optical lattices has opened a doorway to engineering various kinds of Chern insulators, using the paradigm of shaken optical lattices and the Floquet formalism, and studying topological transitions in them [67,69,86]. These realizations offer an appreciable degree of tunability and provide an encouraging platform arXiv:1709.08354v2 [cond-mat.mes-hall] 17 Jan 2018 for the study of Haldane systems under periodic driving.…”
Section: Introductionmentioning
confidence: 99%